2005
DOI: 10.1139/x05-001
|View full text |Cite
|
Sign up to set email alerts
|

Invertebrate predation of postdispersal seeds and juvenile seedlings of black spruce (Picea mariana) in the boreal forest of eastern Canada

Abstract: We used an extensive vertebrate exclosure experiment to evaluate black spruce (Picea mariana (Mill.) B.S.P.) postdispersal seed and seedling predation by invertebrates in three boreal habitats of Eastern Canada: recent burn, spruce–moss, and lichen woodland. Between 9% and 19% of seeds were eaten by invertebrates. Seed predation was higher in recent burns than in spruce–moss and lichen woodlands. Abundance and diversity of potential invertebrate seed consumers sampled in pitfall traps also varied among habitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 22 publications
3
18
1
Order By: Relevance
“…In contrast to the findings of Côté et al (2003Côté et al ( , 2005, seedlings were not lost to herbivory by small rodents in this study, confirming that vertebrate predation did not affect forest regeneration in the first 2 years following the Rocky Pond burn. Côté et al (2003Côté et al ( , 2005 found that up to 31% of black spruce seedlings were lost as a result of rodent herbivory, emphasizing variation in level of predation across geographic areas, which may reflect small mammal population levels.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In contrast to the findings of Côté et al (2003Côté et al ( , 2005, seedlings were not lost to herbivory by small rodents in this study, confirming that vertebrate predation did not affect forest regeneration in the first 2 years following the Rocky Pond burn. Côté et al (2003Côté et al ( , 2005 found that up to 31% of black spruce seedlings were lost as a result of rodent herbivory, emphasizing variation in level of predation across geographic areas, which may reflect small mammal population levels.…”
Section: Discussionsupporting
confidence: 71%
“…Abiotic factors such as soil moisture, soil temperature, and relative humidity influence desiccation rates of seedlings following fire (Castro et al 2004), while biotic factors such as seedling herbivory can affect survival and limit recruitment (Hulme 1996;Albrectsen et al 2004). Small rodents and slugs are common seedling herbivores that can negatively affect coniferous seedling survival and recruitment and have accounted for losses of upwards of 20% of seedlings across a range of unburned boreal habitats Granström 1997, 2000;Noel 2004;Côté et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that a relative scarcity of food in this habitat could make the seedlings more attractive to predators, but further testing is necessary to confirm this hypothesis. Some seedlings inside exclosures were also damaged, possibly by invertebrate predators such as native slugs present at these sites that are known to feed on P. mariana seedlings (Côté et al 2005;Wheeler 2009). Pathogens, intense precipitation, and wind are other possible sources of damage that need to be further investigated, and it would not be unexpected that the latter two of these factors would be more prevalent in the more exposed higher elevation habitats.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of evidence indicating that rodents were able to breach our exclosure material suggested that seed losses from within exclosures reflected activity of invertebrate seed predators, including ants (Hymenoptera: Formicidae) and ground beetles (Coleoptera: Carabidae; Côté et al 2005). The habitats most different in terms of structure, maple forests and old Germination and growth occurred in an environmental chamber.…”
Section: Discussionmentioning
confidence: 99%